Racial differences in prevention decision making among U.S. women at high risk of breast cancer: A qualitative study. - Tasleem J Padamsee; Anna Muraveva; Rachel J Meadows; Megan Hils; Lisa D Yee; Celia E Wills; Electra D Paskett (PLoS ONE, 2023)
Purpose Women at high risk of breast cancer face complex decisions about how to manage those risks. Substantial gaps in current knowledge include how women make these decisions and how decision making may differ across sub-populations. Among these critical gaps are the questions of (a) whether racial differences exist between the experiences of high-risk women navigating breast cancer risk, and (b) what consequences those racial differences might have on women's ability to manage their cancer risks. The present study is designed to address these questions directly. Methods Fifty semi-structured interviews were conducted with high-risk Black (n = 20) and white women (n = 30) between May 2015 and March 2016 in person in Ohio and by phone. Transcribed data were analyzed using grounded theory methods. Main findings Our analyses suggest that many of the core decision-making dynamics high-risk women navigate differ by race. The experiences of white and Black women in our study differ in terms of (a) contextualizing risk-how women make sense of their own breast cancer risk, the degree to which they worry about risk, and how they prioritize risk within the contexts of their broader lives; (b) conceptualizing risk management-how, how much, and from whom women learn about and conceptualize their options for preventing cancer and/or ensuring that cancer gets diagnosed early; and (c) constraints-the external barriers women face throughout their decision-making and risk-management processes. In sum, the Black women we interviewed reported feeling less well-situated to consider and cope actively with breast cancer risk, less well-informed about risk-management options, and more constrained in their use of these options. Conclusions High-risk women's accounts of the complex dynamics that shape breast cancer prevention decisions suggest that these dynamics vary substantially by race, such that Black women may experience disadvantages relative to whites.